The Number of Bacteria Colonies in Carp Fish (Cyprinus carpio) After Administration of Lime (Citrus aurantifolia) and Orange Extract (Citrus jambhiri Lush.) - Lubis, Nenni Dwi Aprianti (Journal of Saintech Transfer, 2022)
Fish is one of the most commonly consumed protein sources. Fish are at risk as a medium for the growth of microbial contaminants that can cause foodborne diseases. This disease can cause diarrhea and even death.Contaminant microbes can be found in foods consumed raw, such as Naniura, a typical Batak cuisine in the form of raw carp. Various natural spices such as lime and orange also have potential as antimicrobials. This study aimed to determine the antimicrobial potential of lime and orange juice in fresh carp samples. This study used extracts of lime and orange with concentrations of 6.25%, 12.5%, 25%, and 50%, respectively. The sample used is carp meat. The bacteria present in the sample were counted using the Total Plate Count (TPC) method before and after lime and lime extract administration. The results showed that before administering the two extracts, the total colonies in the sample could not be counted. The antimicrobial effect of orange juice extract began to be seen at a concentration of 12.5%, while in lime, it was only seen at a concentration of 50%. From the results of this study, it was concluded that orange juice extract had a better antimicrobial effect than lime.